Inflation Dynamics and Global Value Chains - de Soyres, Francois (World Bank, Washington, DC, 2019)
The global economy has witnessed a decline in inflation and an increase in inflation synchronization since the early 1980s. This paper investigates the relationship between inflation synchronization and trade integration, and documents the strong link between inflation co-movement and Global Value Chain (GVC) participation. Using 35 years and both gross and value-added trade flows, evidence shows that an increase in production linkages, as proxied by trade in intermediate inputs, is strongly associated with higher inflation correlation. Moreover, backward GVC participation is associated with an increase in bilateral inflation co-movement while forward participation is linked with a higher correlation between domestic and worldwide inflation. The paper also finds evidence of the effect of trade integration in decreasing inflation levels.